Pengaruh Kepemilikan Manajerial, Institusional, Asing, Terkonsentrasi Terhadap Audit Delay Pada Perusahaan yang terdaftar dalam BEI (Bursa Efek Indonesia) - Hermansyah, Geraldo Ghiffari (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
The purpose of this study is to examine whether the influence of Managerial Ownership, Institutional Ownership, Foreign Ownership, and Concentrated Ownership on Audit Delay in Companies Listed on the Indonesia Stock Exchange. The population taken is all the Company's financial statements registered on the IDX in the last 8 years, the sample obtained is 51 financial statements of the Company. The data was processed using the SPSS application using the multiple linear analysis test method and the classical assumption test. In the test results, it was explained that Managerial Ownership (X1) has a significant influence on Audit Delay (Y). Meanwhile, Institutional Ownership (X2), Foreign Ownership (Xv), and Concentrated Ownership (X4) have no effect on Audit Delay (Y)